Analysis Of The Need For Start Assistants For Deaf Swimmers - Ika Novitaria Marani; Ari Subarkah; Setyo Purwanto; Adi Wijayanto (UNIVERSITAS NEGERI MAKASSAR, 2023)
Persons with disabilities were people who had long-term physical, mental, intellectual or sensory limitations. People with disabilities were divided into several types, namely physical disabilities, sensory disabilities, mental disabilities, and intellectual disabilities. Deaf people are included in sensory disabilities who have limited senses. So people with disabilities need special assistance, especially in starting swimming. The purpose of this study was to determine whether deaf swimmers need a swimming start aid. The research method used was a descriptive method with a survey technique. The time of study was carried out in 2022 starting from April to July. The location for data collection was carried out at the Senen Jakarta swimming pool. The population and samples used were athletes with hearing impairment in DKI Jakarta, totalling 20 people using total sampling. The research instrument used was a questionnaire to analyze the need for start aids for deaf swimmers by having three indicators as a decision maker on whether or not to use start aids for deaf swimmers. The data analysis technique used was the descriptive analysis technique. The results showed that deaf swimmers needed a start aid. Further research is expected to be able to make starting aids that can be used by deaf swimmers to achieve optimal performance.